Empowering rural communities: a library outreach strategy in Bayambang, Pangasinan for livelihood improvement - Villanueva, Mike James O.
Farmers in marginalized rural communities require agricultural information tailored to their specific needs. Aiming to enhance agricultural practices and improve rural livelihood through a library outreach strategy, this study investigates the information needs and dissemination strategies for farmers in Barangay Amancosiling Norte, Bayambang, Pangasinan. Using a qualitative descriptive research design, semi-structured interviews with farmers and information providers were conducted to identify key information needs and the factors influencing information poverty. The findings highlight significant challenges, such as language barriers and the complexity of technical information that highlights the necessity for localized, easily understandable content presented in the local language with visual aids. The study underscores the importance of developing context-specific information materials and offers a framework for effective agricultural information dissemination through libraries.